Etične dileme pri določanju ciljev v rehabilitaciji - Kos, Nataša (Rehabilitacija (Ljubljana), 2018)
Introduction: When discussing goals of rehabilitation, the patients and his/ her right to take part in the goal setting process is always in the focus of attention. Methods: We reviewed the literature available online (via PubMed bibliographic database). Our goal was to assess the importance of goal setting in rehabilitation medicine and the emergence of ethical dilemmas in connection with goal setting. Results: We found 49 articles, of which we used 20 for further analysis. The reviewed literature states that goal setting is necessary when planning treatment procedures and when assessing the efficacy of the treatment. The articles mention the possibility of emergence of ethical dilemmas due to differences between the medical team and the patient, the patient%s family and the medical team, and due to different opinions among different team members. Discussion: Goals are important in rehabilitation and required for planning treatment procedures. Realistic and achievable goals must be set. The wishes of the patients, as well as the goals they wish to achieve, are not always consistent with realistically achievable goals. This leads to an ethical dilemma. For members of the rehabilitation team, reaching an agreement with the patient about the level of achievable improvement while respecting his/her autonomy and the principle of always doing good, may pose a substantial ethical challenge. The patient%s family often harbours unrealistic expectations, which also lead to difficulties that need to be resolved. An important and often mentioned ethical dilemma is that members of the rehabilitation team have different opinions about appropriate goal setting, as well as the choice of different rehabilitation procedures for the patient. Conclusion: Ethical dilemmas arising in connection with goal setting can only be solved by good communication.
Keywords: cilji; ethical dilemmas; etične dileme; Goals; rehabilitacija; Rehabilitation; vocational rehabilitation